Mental Toughness in Sports a Research on Cycling Athletes - Hüseyin Bilgin; Hayri Demir; Fatih Harmancı (Selcuk University, 2022)
The aim of this study is to determine how much resistance of national and non-national athletes interested in cycling is affected. The universe of the research is interested in establishing a license for cycling of Turkish athletes, and a total of 100 riders, including sample group, 50 national and 50 national, are created. Participating cyclists Sheard and Ark to determine mental endurance. (2009), developed by Altıntaş and Kuruc in 2016, was used in the Sports mental retardant.according to various variables. Mental endurance scores of riders;according to various variables (gender, age,year of making sports, national and internationaldegrees in competitions)descriptive statistics (frequency, arithmetic mean, standard deviation);t, one-way analysis of variance (ANOVA) was evaluated according to Tukey multiple comparison tests. Participating in the researchcycling athletes, score averages of mental enduranceyear of making sports,gender, agewhile there were statistically significant differences among the national level, there was no significant difference in international degrees.